KURIKULUM PENDIDIKAN AGAMA ISLAM BERBASIS INTEGRASI PESANTREN-MADRASAH DI MTS NURUL UMMAH KOTAGEDE - M Faishal Khoirurrijal (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2020)
This research is motivated by the application of Islamic Education curriculum based on the integration of pesantren-madrasah in MTs. Nurul Ummah Kotagede Yogyakarta. The purpose of this research was to find out the main factor of the application of the Islamic Religious Education curriculum based on the integration of Islamic Education curriculum based on the integration of pesantren-madrasah in MTs. Nurul Ummah and how the model is applied. The results of this research showed that: 1) The main factor that resulted in implementation of the Islamic Education curriculum based on the integration of pesantren-madrasah in MTs. Nurul Ummah is due to the similarities between Islamic Education materials in MTs. Nurul Ummah with religious materials in the Nurul Ummah Islamic Boarding School for Students. 2) The model that used in the Islamic Education curriculum based on the integration of pesantren-madrasah in MTs. Nurul Ummah is within single diciplines, which is by combining the Diniyah subjects in the Nurul Ummah Islamic Boarding School for Students that have similarities with the Islamic Education subjects in MTs. Nurul Ummah which includes Al-Qur'an Hadis, Akidah Akhlak , Fikih, and Sejarah Kebudayaan Islam.